Changes in secondary metabolism and deposition of an unusual lignin in the ref8 mutant of Arabidopsis - Franke, Rochus; Hemm, Matthew R.; Denault, Jeff W.; Ruegger, Max O.; Humphreys, John M.; Chapple, Clint (The Plant journal : for cell and molecular biology, 2002)
Summary The end products of the phenylpropanoid pathway play important roles in plant structure and development, as well as in plant defense mechanisms against biotic and abiotic stresses. From a human perspective, phenylpropanoid pathway‐derived metabolites influence both human health and the potential utility of plants in agricultural contexts. The last known enzyme of the phenylpropanoid pathway that has not been characterized is p‐coumarate 3‐hydroxylase (C3H). By screening for plants that fail to accumulate soluble fluorescent phenylpropanoid secondary metabolites, we have identified a number of Arabidopsis mutants that display a reduced epidermal fluorescence (ref) phenotype. We have now shown that the ref8 mutant is defective in the gene encoding C3H. Phenotypic characterization of the ref8 mutant has revealed that the lack of C3H activity in the mutant leads to diverse changes in phenylpropanoid metabolism. The ref8 mutant accumulates p‐coumarate esters in place of the sinapoylmalate found in wild‐type plants. The mutant also deposits a lignin formed primarily from p‐coumaryl alcohol, a monomer that is at best a minor component in the lignin of other plants. Finally, the mutant displays developmental defects and is subject to fungal attack, suggesting that phenylpropanoid pathway products downstream of REF8 may be required for normal plant development and disease resistance.